2015
DOI: 10.1007/s11356-015-5683-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface capping and size-dependent toxicity of gold nanoparticles on different trophic levels

Abstract: In the present study, the toxicity of gold nanoparticles (Au NPs) was evaluated on various trophic organisms. Bacteria, algae, cell line, and mice were used as models representing different trophic levels. Two different sizes (CIT30 and CIT40) and surface-capped (CIT30-polyvinyl pyrrolidone (PVP)-capped) Au NPs were selected. CIT30 Au NP aggregated more rapidly than CIT40 Au NP, while an additional capping of PVP (CIT30-PVP capped Au NP) was found to enhance its stability in sterile lake water medium. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 67 publications
0
41
0
Order By: Relevance
“…Particle size has been demonstrated to determine the toxicity and distribution of AuNPs, which has aroused considerable attention in the biomedical field (Iswarya et al . ; Li et al . ).…”
Section: Toxicity Of Aunpsmentioning
confidence: 99%
“…Particle size has been demonstrated to determine the toxicity and distribution of AuNPs, which has aroused considerable attention in the biomedical field (Iswarya et al . ; Li et al . ).…”
Section: Toxicity Of Aunpsmentioning
confidence: 99%
“…People take the preparation and synthetic of Nano‐CdS very seriously, and are paying more attention to the adverse effects of nanomaterials on human‐health and environment . At present, a growing number of scholars at home and abroad turn to focus on the research of the toxicity of nanomaterials . And a lot more are focusing on oxidative damage and the general toxicity studies .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al reported that CdS nanodots and nanorods had significant different toxicities on mice testis, kidney, and liver; they also had different genotoxicity toxicity. All the differences could be explained not only by the differences in their Cd 2+ release patterns but also by particle morphology …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations